2021
DOI: 10.3389/fnut.2021.718792
|View full text |Cite
|
Sign up to set email alerts
|

Higher Animal Protein Intake During the Second Trimester of Pregnancy Is Associated With Risk of GDM

Abstract: Background and Aims: This study aimed to examine the associations between the total protein intake as well as types and sources of proteins with the gestational diabetes mellitus (GDM) risk.Method and Results: This was a prospective cohort study of the pregnant women in Malaysia. In this study, the total, animal, and plant protein intakes were assessed using a semi-quantitative food frequency questionnaire. Of the 452 women, 48 (10.62%) were diagnosed with GDM. From pre-pregnancy to second trimester, most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In accordance with our study, a prospective evaluation in the Nurses' Health Study II, which included 21,457 mothers with singleton pregnancies, found that mothers in the highest quintile of total red meat consumption had twice the risk of GDM than mothers in the lowest quintile 21 . Higher consumption of animal-based proteins, especially those from red meat, in the second trimester of pregnancy was highly related to the risk of developing GDM, according to a prospective cohort study of 452 pregnant women in Malaysia 22 . Furthermore, more red meat consumption during the second trimester of pregnancy was linked to an increased risk of GDM, according to a Chinese cohort study; however, there was no link between red meat consumption during the first trimester and that risk 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our study, a prospective evaluation in the Nurses' Health Study II, which included 21,457 mothers with singleton pregnancies, found that mothers in the highest quintile of total red meat consumption had twice the risk of GDM than mothers in the lowest quintile 21 . Higher consumption of animal-based proteins, especially those from red meat, in the second trimester of pregnancy was highly related to the risk of developing GDM, according to a prospective cohort study of 452 pregnant women in Malaysia 22 . Furthermore, more red meat consumption during the second trimester of pregnancy was linked to an increased risk of GDM, according to a Chinese cohort study; however, there was no link between red meat consumption during the first trimester and that risk 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It also underscored the importance of the carbohydrates source. Except for carbohydrates quality, the source of protein and fat in plant-based dietary patterns mattered, too [ 68 , 69 ]. Pregestational low-carbohydrate diets with high protein and fat from animal foods were positively associated with the risk of developing GDM, nevertheless, low-carbohydrate diets with high protein and fat from vegetable foods were inversely related to the risk of developing GDM [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregestational low-carbohydrate diets with high protein and fat from animal foods were positively associated with the risk of developing GDM, nevertheless, low-carbohydrate diets with high protein and fat from vegetable foods were inversely related to the risk of developing GDM [ 70 ]. In detail, higher animal protein intake would increase the risk of developing GDM, whereas higher plant protein intake would do not [ 68 ]. In addition, higher fat intake, whether animal fat or plant fat, would increase the risk of developing GDM [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have shown that higher animal protein intake during pregnancy (> 42.2 g/day), particularly red meat, is associated with an increased risk of gestational diabetes [ 109 ]. Further concerns surround the impact of long-term maternal nutritional ketosis and its potential negative impact on foetal neural development and organ damage [ 108 , 110 , 111 ].…”
Section: Gestational Diabetesmentioning
confidence: 99%